Performance comparison between ZSI and SL-ZSI based axial flux permanent magnet synchronous generator wind energy conversion system for different wind speeds with different PWM methods - Ramesh babu, V; Srinivasa rao, J; Ranjit, M; Vijayarama rao, S (International Journal of Engineering and Technology, 2026)
In this paper the performance comparison between Impedance source Inverter (ZSI) and Switched Inductor Impedance Source Inverter(SL ZSI )based Axial Flux Permanent Magnet Synchronous Generator(AFPMSG) wind energy conversion system for different wind speeds with different PWM methods are discussed. The generator generates different voltage values for different wind speeds. The Switched Inductor Z-Source Inverter performance is analyzed for various voltage values of AFPMSG. This is done to predict suitable inverter and to reduce the conversion stages of the Wind Energy Conversion System. For comparison analysis voltage gain, Switching stress and Total Harmonic Distortion (THD) are taken into consideration. Axial Flux Permanent Magnet Machines are characterized by the short axial length and high power to weight ratio and hence these machines facilitate direct compact integration with the wind turbine, The key features like high efficiency, high power density, elimination of gearbox and fast dynamic response make this kind of machines very attractive for Wind application. By connecting more number of inductors and diodes to the Z-Source inverter bridge, multi cell Switched Inductor Z-Source Inverter is formed, and it can boost voltage nearly two times more than conventional ZSI with the same shoot through duty ratio. Hence the switching stress on the Z capacitors and Inverter bridge get reduced. Thus, the proposed topology require less power electronic switches, and more reliable under short circuit. The simulation readings are compared for different wind speeds and for all three PWM methods to identify which is the best PWM method for SL ZSI.